UPAYA INDIA DALAM MENDORONG INVESTASI ASING DAN PERDAGANGAN DI SUDAN TAHUN 2002 – 2011 - Yulia Dewi, Ni Ketut Leony; Fasisaka, Idin; Widya Nugraha, A. A. Bagus Surya (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2019)
ABSTRACT The 'Focus Africa' program launched after India's economic liberalization in 1991 had a significant impact on India's economic growth. The aim is to find new markets and natural resources for Indian private and public businesses. Sudan became one of the countries chosen because it has abundant natural resources, especially petroleum. Besides that Sudan is one of the countries with the most population in Africa. This research uses a qualitative method with data collection techniques through literature study. Data will be analyzed by descriptive analysis method using commercial diplomacy concept. Based on the analysis, concluded that India's efforts to encourage foreign direct investment and trade in Sudan through commercial diplomacy can be maximized through; Trade Promotion, Promotion of Foreign Direct Investment, Co-operation in Science and Technology, Advocacy for National Business Community, Networking & Public Relations and Contract Negotiator of Implementation. Keywords:Commercial Diplomacy, Foreign Direct Investment, Trade